TO COMPARE THE EFFICACY(response rate) OF HIGH DOSE DEXAMETHASONE WITH CONVENTIONAL PREDNISOLONE IN THE TREATMENT OF NEWLY DIAGNOSED ADULT PATIENTS OF IMMUNTHROMBOCYTOPENIA PURPURA - Butt, Batool; Qayyum, Uzma; Butt, Hareem; ahsan, Omar; Farooq,; Erum, Humaira; Jawwad Khan, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Immune thrombocytopenic purpura with multimodal incidence having peaks in each age groups is a chronic clinical syndrome in adults, with disease more predominant in females in adults. The aim of the study was to compare the efficacy (response rate) of high dose dexamethasone with conventional prednisolone in the treatment of newly diagnosed adult patients of Immune thrombocytopenic purpura. It was a prospective quasi-experimental study, conducted at the Department of Medicine of a tertiary care hospital from Jan to Dec 2019. Subjects and Methods: The sample population comprised of 130 cases of newly diagnosed ITP patients, having platelet count <30,000/ul with or without bleeding symptoms who received either dexamethasone (40 mg/day for 04 days) or prednisolone (0.5-1 mg/kg PSL for 01 week). Treatment response was measured at day 7. Results: Out of 130 patients 65 patients were treated with dexamethasone and 65 patients with prednisolone .83.08% (n=54) cases in Group-A and 33.85% (n=22) in Group-B had response while remaining 16.92% (n=11) in Group-A and 66.15% (n=43) in Group-B had no response. The p value was calculated as 0.000 which shows a significant difference. Conclusion: We concluded that high dose of dexamethasone shows a significantly higher response when compared with conventional prednisolone in the treatment of newly diagnosed adult patients of Immune thrombocytopenia purpura.